2008
DOI: 10.1016/j.physletb.2008.10.034
|View full text |Cite
|
Sign up to set email alerts
|

In-medium pion and partial restoration of chiral symmetry

Abstract: The partial restoration of chiral symmetry in nuclear medium is investigated in a model independent way by exploiting operator relations in QCD. An exact sum rule is derived for the quark condensate valid for all density. This sum rule is simplified at low density to a new relation qq * / qq = (F t π /Fπ)Z * 1/2 π with the in-medium quark condensate qq * , in-medium pion decay constant F t π and in-medium pion wave-function renormalization Z * π . Calculating Z * π at low density from the iso-scalar pion-nucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 36 publications
4
70
0
Order By: Relevance
“…If so, it would affect the mesonic spectrum, and, in particular, the mass of the η meson could decrease by a significant amount. It is also argued that in nuclear medium, the chiral condensate drops about 30% at the normal nuclear density [3], which could also imply a partial restoration of the U A (1) symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…If so, it would affect the mesonic spectrum, and, in particular, the mass of the η meson could decrease by a significant amount. It is also argued that in nuclear medium, the chiral condensate drops about 30% at the normal nuclear density [3], which could also imply a partial restoration of the U A (1) symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…m π , M and µ are the mass of the pion, the nucleus and the reduced mass respectively. The isovector b 1 parameter is theoretically known to be related to the order parameter of spontaneous chiral syemmmtry breaking, chiral condensate [1][2][3][4]. In the deeply bound pionic atoms, the pion is partly embeded inside the nucleus and in-medium b 1 parameter is deduced from the binding energy and the width.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can investigate the in-medium value of chiral condensate. The deeply pionic atoms were studied in GSI by using missing-mass spectroscopy of the (d, 3 He) reactions. Pionic states with 205,207 Pb [5][6][7][8] and 115,119,123 Sn [9] were measured and it was concluded that b f ree 1 /b med 1 = 0.78 ± 0.05, where b med…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful example is high precision spectroscopy of pionic atoms [14,15], and an advanced experiment in conjunction with theoretical investigations [16][17][18][19] provided quantitative information on the chiral symmetry breaking and its partial restoration in a nuclear medium based on the precision data [20]. The deduced order parameter of the chiral symmetry, chiral condensate ⟨qq⟩, at the nuclear saturation density ρ 0 presented reduction of ∼ 30% compared to that in the vacuum.…”
Section: Introductionmentioning
confidence: 99%